The Transformation of State-Owned Enterprise Monopolies and Healthy Market Competition in Bulding Harmonization of Business Competition Law - Joyo Santoso, Budi; Hamid, Adnan; Suasoongnern, Sineenart (Journal Evidence Of Law, 2025)
The 1945 Constitution, Article 33(2), establishes the state as the controller of important branches of production for the welfare of the people, but its implementation has continued to shift in line with political regime dynamics, from the command economy model of independence to the corporatization of state-owned enterprises (SOEs) under the New Order and the post-1998 crisis reforms that emphasized healthy competition. The latest debate has emerged from Law No. 1/2025 on SOEs, which grants the President discretionary monopoly powers through Government Regulations without competition impact assessments by the Competition Commission (KPPU), while Law No. 5/1999 requires SOE monopolies to be regulated by law and supervised by the KPPU. The main issue is the normative disharmony between executive monopoly rights and independent oversight mechanisms, which creates legal uncertainty, potential inefficiency, and rent-seeking risks. This study employs a normative-analytical legal approach with literature review and analysis of primary, secondary, and tertiary legal documents, integrating the statute approach and conceptual approach to unravel the relationship between the constitutional framework, monopoly policy, and the principle of fair competition. The findings indicate that Article 86M of Law 1/2025 expands executive discretion without adequate checks and balances, while Law 5/1999 provides a strict oversight framework through the KPPU. The discussion emphasizes the urgency of regulatory harmonization through systematic revision of Article 86M, including mandatory consultation with the KPPU, a sunset clause, and a competition impact assessment, as well as strengthening the independence and advisory role of the KPPU. The implementation of Good Corporate Governance, objective criteria for “national interest,” and periodic evaluation mechanisms will ensure that state-owned enterprise monopolies function in accordance with the objectives of the welfare state without undermining the competitive environment. A phased implementation model over 10 years recommends normative, institutional, operational, and democratic arrangements to achieve a balance between state intervention and sustainable market mechanisms.